2005
DOI: 10.1097/01.ccm.0000178183.21883.23
|View full text |Cite
|
Sign up to set email alerts
|

The use of dexmedetomidine to facilitate acute discontinuation of opioids after cardiac transplantation in children*

Abstract: To our knowledge, this report describes the first use of dexmedetomidine to facilitate opioid withdrawal in children with a cardiac transplant. Dexmedetomidine allowed for the preservation of satisfactory hemodynamic parameters during acute withdrawal from opioids in children with denervated hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…For example, the need for continued sedation to prevent an uncontrolled or accidental extubation often confl icts with the desire to decrease sedation to the point where a child is awake enough to attempt extubation. Anecdotally, we and others have found that the use of a short-acting agent such as propofol or dexmedetomidine facilitates opioid or benzodiazepine withdrawal during the periextubation period (Wheeler, unpublished data) [238][239][240][241]. Typically, dexmedetomidine or propofol is initiated as the dosage of opioid and benzodiazepine infusions are rapidly deescalated, usually approximately 6-12 hr before a trial of extubation.…”
Section: Tracheal Extubationmentioning
confidence: 97%
“…For example, the need for continued sedation to prevent an uncontrolled or accidental extubation often confl icts with the desire to decrease sedation to the point where a child is awake enough to attempt extubation. Anecdotally, we and others have found that the use of a short-acting agent such as propofol or dexmedetomidine facilitates opioid or benzodiazepine withdrawal during the periextubation period (Wheeler, unpublished data) [238][239][240][241]. Typically, dexmedetomidine or propofol is initiated as the dosage of opioid and benzodiazepine infusions are rapidly deescalated, usually approximately 6-12 hr before a trial of extubation.…”
Section: Tracheal Extubationmentioning
confidence: 97%
“…Although it is not approved for use in children, dexmedetomidine is gaining popularity in pediatrics, and its administration has been reported in small series [2][3][4][5]. We report the use of dexmedetomidine in a neonate whose repair of bladder exstrophy required prolonged sedation and minimal mobility postoperatively.…”
Section: Introductionmentioning
confidence: 93%
“…Reasons to initiate dexmedetomidine included high opioid requirements and development of undesirable side effects, pain unresponsive to escalating doses of opioid, and the clinical impression that in part, opioid-induced hyperalgesia was contributing to patient's pain. Given previous reports that dexmedetomidine facilitates opioid weaning 15,16 and has profound analgesic and sedative effects 12,14 , a decision to initiate dexmedetomidine was made. As suggested by Figure 1, daily oral morphine-equivalent intake was markedly reduced after the initiation of dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine decreases opioid consumption and pain intensity 12,14 , and in settings where patients are on high-dose opioids, dexmedetomidine halts escalation of opioid intake and facilitates opioid weaning 15,16 . There are a few reported cases of dexmedetomidine use in SCD patients in emergency rooms and during the perioperative period 17,18 .…”
Section: Introductionmentioning
confidence: 99%